Developing Stakeholder Engagement for Infrastructure Projects: Case Study on Indonesia Infrastructure Roundtable/IRR - Widianingrum, Ratna (PT Penjaminan Infrastruktur Indonesia (Persero), 2018)
The relatively high economic growth leads to an increase in infrastructure needs in Indonesia. Providing these needs for infrastructure has an irreplaceable role in improving the overall quality of life of the population, therefore its success requires support and commitment from various stakeholder groups. In the context of the support, a concept to approach the stakeholders is known as stakeholder engagement. The objective of this research is to measure the effectiveness of a program in affecting the condition of stakeholders, and in developing the stakeholder engagement which will directly determine the success of infrastructure development. This study was conducted using a qualitative descriptive method through case study approach to observe the relationship between the use of stakeholder-involvement program and the level of stakeholder engagement. The results show that the quality of activities (procedural quality, responsiveness quality, quality of outcomes) shows relatively good results with a middle-level involvement. It will require more activities to trigger a more intense relationships and to increase the level of stakeholder engagement in providing their support for infrastructure development.